Dyeing of cotton with natural dyes from Bluebell vine, Globe amaranth, Marigold and Shoe flower - Sreeranjini, S.; Pradeep, P S Akshaya (International Journal of Scientific Research in Biological Sciences, 2019)
Natural dyes are known for their use in coloring of food substrate, leather as well as natural fibers like wool, silk and cotton as major areas of application since pre-historic times. In the present study, dyeing pigments were extracted from the flowers of blue bell vine, globe amaranth, marigold and shoe flower and application on cotton fabrics were analyzed. Two mordants ferrous sulphate and copper sulphate were used. The result revealed that different shades were obtained from the dyes when subjected to mordant treatments. Dyes obtained from these flowers can be utilized for various industries such as textile, cosmetics, leather, food and pharmaceuticals.